2012
DOI: 10.1523/jneurosci.0013-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Type 5 Metabotropic Glutamate Receptors and Diacylglycerol Lipase-  Initiates 2-Arachidonoylglycerol Formation and Endocannabinoid-Mediated Analgesia

Abstract: Acute stress reduces pain sensitivity by engaging an endocannabinoid signaling circuit in the midbrain. The neural mechanisms governing this process and molecular identity of the endocannabinoid substance(s) involved are unknown. We combined behavior, pharmacology, immunohistochemistry, RNA interference, quantitative RT-PCR, enzyme assays, and lipidomic analyses of endocannabinoid content to uncover the role of the endocannabinoid 2-arachidonoyl-sn-glycerol (2-AG) in controlling pain sensitivity in vivo. Here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 52 publications
4
67
0
Order By: Relevance
“…Detailed study of this effect revealed the mobilisation of both AEA and 2-AG in the periaqueductal grey matter (111) , and suggested that 2-AG acting at CB 1 receptors was the predominant mechanism. Additional work indicated that further enhancing stress-induced EC signalling via FAAH or MAGL inhibition produces still greater anti-nociceptive effects (112,113) , and confirmed the pivotal role of 2-AG signalling in the periaqueductal grey matter (114) . The involvement of stress in human pain responses and the presence of an EC-mediated mechanism are now being studied clinically (115) .…”
Section: Supra-spinal Mechanismsmentioning
confidence: 73%
“…Detailed study of this effect revealed the mobilisation of both AEA and 2-AG in the periaqueductal grey matter (111) , and suggested that 2-AG acting at CB 1 receptors was the predominant mechanism. Additional work indicated that further enhancing stress-induced EC signalling via FAAH or MAGL inhibition produces still greater anti-nociceptive effects (112,113) , and confirmed the pivotal role of 2-AG signalling in the periaqueductal grey matter (114) . The involvement of stress in human pain responses and the presence of an EC-mediated mechanism are now being studied clinically (115) .…”
Section: Supra-spinal Mechanismsmentioning
confidence: 73%
“…Low to moderate levels of CB 1 receptors have been found in the midbrain periaqueductal gray (PAG), where the ECS is involved in the control of pain sensation, including stress-induced analgesia Hohmann et al 2005;Gregg et al 2012). In contrast to opiate receptors on GABAergic aqueductal neurons, CB 1 receptors are preferentially, but not exclusively, localized in the dorsal portion of the PAG (Tsou et al 1998a;Azad et al 2001).…”
Section: Periaqueductal Graymentioning
confidence: 99%
“…Stimulation of the DAP, particularly following stress, relies in part on cannabinoid receptor type-1 (CB 1 ) activation by the endocannabinoid 2-arachidonoylglycerol (2-AG), which disinhibits PAG output neurons through retrograde inhibition (Ohno-Shosaku and Kano, 2014) of GABA release from interneurons (Hohmann et al, 2005;Gregg et al, 2012). Orexinergic neurons of the lateral hypothalamus project to the vlPAG (Peyron et al, 1998;van den Pol et al, 1998), where activation of orexin type-1 receptors (OX1-R) by orexin-A (OX-A) stimulates 2-AG biosynthesis via the phospholipase C-diacylglycerol lipase α (DAGLα) route, thus potentially producing analgesia (Ho et al, 2011;Watanabe et al, 2005;Azhdari-Zarmehri et al, 2013).…”
Section: Introductionmentioning
confidence: 99%